COMPARISON OF GRAMMATICAL GENDER ON ENGLISH AND OTHER FOREIGN LANGUAGES - Aliqulova Nozimaxon Anvar qizi (TADQIQOTLAR.UZ, 2024)
Annotation: Scientific research on "grammatical gender" in English and other foreign language grammar is a fascinating topic for our researchers to study. This article's goal is to examine the linguistic research that scientists have conducted on the topic of "gender" in the languages of Russia and England, as well as the connections between these studies. an extensive examination of pertinent theories found in Russian and English literature. vocabulary and methods utilised in each language; a comparison and contrast with instances is intended.